The use of calcium carbide in food and fruit ripening: Potential mechanisms of toxicity to humans and future prospects. (28th February 2022) - Okeke, Emmanuel Sunday; Okagu, Innocent Uzochukwu; Okoye, Charles Obinwanne; Ezeorba, Timothy Prince Chidike
Highlights: Using CaC2 to hasten fruit ripening results in acute and chronic toxic consequences. This article presents up-to-date knowledge on the mechanism of CaC2 toxicity. Current detection methods for CaC2 and its impurities (As) were reviewed in-depth. Nutritional and biochemical alterations in fruits caused by CaC2 were discussed. Strategies for mitigating the use of CaC2 and its adverse effects were suggested. Abstract: The global increase in the demand for ripe fruits has induced unhealthy use of toxic chemicals in fruit ripening. One of such chemicals in common use is calcium carbide (CaC2 ). Due to its nature, commercial CaC2 is consistently found to contain impurities such as Arsenic and other toxic and carcinogenic chemicals. Few studies have only reported acute associative effects of CaC2, whereas there is only sparse evidence of its chronic and long-term impact. This article reviewed all the information on the nature of commercial CaC2 used for food processing. Meanwhile, all reports on the acute effects of CaC2, such as skin burns, skin irritations and inflammation, were summarized. Despite reported acute cases, an increase in commercial CaC2 for fruit ripening has been reported in recent times, especially in developing countries, as many vendors may consider the toxic effects/risks as negligible. Therefore, this study highlighted the paucity in research studies on the chronic impact of commercial CaC2 while proposing possible mechanisms for CaC2 induction of cancer, cardiovascular dysfunction, diabetic mellitus and others. Furthermore, suggestions on further studies to unravel the chronic impacts of CaC2 on health and recommendations for viable alternatives of fruit ripening with minimal or zero toxicity were proffered. Finally, other suggestions such as improving CaC2 detection technologies and innovative grassroots educational programs will strengthen national and international agencies to enforce restrictions on the illicit use of the toxicant for fruit ripening.